Spin evolution and feedback of supermassive black holes in cosmological simulations - Bustamente, Sebastian; Springel, Volker (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. It is well established that the properties of supermassive black holes (BHs) and their host galaxies are correlated through scaling relations. While